(untitled) (Bangladesh Journal of Public Administration, 2022)
Nowadays, no public or private organization in Bangladesh can function without the widespread adoption of social networking platforms. It has recently replaced in-person social interactions and communication. Most modern organizations provide their employees with affordable Internet connections by PC, laptop, and some other mobile devices, allowing them quick access to personal and professional social networking sites from both home and work. There are many advantages to using social networking sites at work, but there are also some negatives. An organizational policy on the use of social networking sites while on the job is a powerful management tool. This research aims to learn more about how employees are utilizing social media at work as well as the effects of this behaviour. The research hopes to help organizations implement policies that are mutually agreeable to employees and management. A total of 60 people from a variety of occupations participated in the survey. Some of the primary ideas given in this paper that can work for the organization without restricting the freedom of the employees are: providing proper direction; teaching and training employees about the security risks for the organization; enabling employees with time-based access; etc. , construction workers.